Konsep Ketuhanan dalam Upaniṣad - I Made Pasek Subawa (Sphatika: Jurnal Teologi, 2021)
The teachings of divinity in the upaniṣads position God as a concept that is personified into various forms of attributes according to the use it has. This shows that God exists and has a duty and function in life. In this situation, a divine identity will emerge, which depends so much on the function it has and depends on how people believe in it, even though in fact God is singular. Man himself is one part in which there is a cause of life which is the smallest part of God, namely the atma. With this atma, humans can actually connect themselves transcendentally with God. This can be done if you are able to carry out sadhana diligently and sincerely.